A novel C-type lectin for Litopenaeus vannamei involved in the innate immune response against Vibrio infection. Issue 135 (April 2023) - Luo, Junliang; Chen, Yanghui; Huang, Yongxiong; Feng, Jiamin; Yuan, Yunhao; Jian, Jichang; Cai, Shuanghu; Yang, Shiping
Abstract: C-type lectins (CTLs), as a member of pattern recognition receptors, play a vital role in the innate immune response of invertebrates to eliminate micro-invaders. In this study, a novel CTL of Litopenaeus vannamei, namely, LvCTL7, was successfully cloned, with an open reading frame of 501 bp and a capability to encode 166 amino acids. Blast analysis showed that the amino acid sequence similarity between LvCTL7 and MjCTL7 ( Marsupenaeus japonicus ) was 57.14%. LvCTL7 was mainly expressed in hepatopancreas, muscle, gill and eyestalk. Vibrio harveyi can significantly affect LvCTL7 expression level in hepatopancreases, gills, intestines and muscles ( p < 0.05). LvCTL7 recombinant protein can bind to Gram-positive bacteria ( Bacillus subtilis ) and Gram-negative bacteria ( Vibrio parahaemolyticus and V. harveyi ). It can cause the agglutination of V. alginolyticus and V. harveyi, but it had no effect on Streptococcus agalactiae and B. subtilis . The expression levels of SOD, CAT, HSP 70, Toll 2, IMD and ALF genes in the challenge group added with LvCTL7 protein were more stable than those in the direct challenge group ( p < 0.05). Moreover, knockdown of LvCTL7 by double-stranded RNA interference downregulated the expression levels of genes ( ALF, IMD and LvCTL5 ) that protect against bacterial infection ( p < 0.05). These results indicated that LvCTL7 had microbial agglutination and immunoregulatory activity, and it was involved in the innate immune response against Vibrio infection in L. vannamei . Highlights: LvCTL7 could directly agglutinate bacterial pathogens. LvCTL7 could regulate the expression of antibacterial-related genes. LvCTL7 is involved in the innate immune response against Vibrio infection.